Family's experience in care patients of end stage kidney disease: Scoping review - Weni Sulastri; Meira Erawati; Dewi Lestari; Novi Lasmadasari; Annisa Pratiwi; Mery Mirna Leni (Universitas Muhammadiyah Semarang, 2023)
Patient caregivers have an important role during and after hemodialysis. caregivers experience barriers and have an impact on bio-psycho-socio-spiritual when providing care. The objective of this study is to summarise the results of several previous studies that provide an overview of the family's experience in care for patients with end-stage kidney disease. This scoping review is a search of electronic databases, Google scholar, ScienceDirect, PubMed, dan research gate. Research (Chronic kidney disease OR chronic kidney disease) AND ('caregiver/psychology' OR caregiver) AND (mental health OR support OR social OR economic OR environmental OR education OR program OR strategy OR services OR care services OR support services. Research from five articles shows that the experience of caregivers caring for patients with the end-stage renal disease over a long period of time has a bio-psycho-socio-spiritual and financial impact on caregivers. Caregivers need support from other families regarding social, physical, psychological, spiritual and economic health that must be met to continue to optimally care for family members who suffer from end-stage kidney disease.